(untitled) (Biological Sciences - PJSIR, 2022)
Cellulose is major source of plant biomass and it can be converted into useful products by cellulases. Fungi are considered as good producer of industrially valued enzymes including cellulases. Current study was carried out to enhance production and characterization of endoglucanase by Aspergillus flavus. Solid state fermentation of sugarcane bagasse was performed and process was optimized for maximum production. Endoglucanase activity was found maximum after 96 h of incubation. Optimum fermentation conditions for the production of endoglucanase by A. flavus were 40 °C temperature, pH 7, 4 mL inoculum size, 50% moisture and 8 g of substrate. There was maximum precipitation of endoglucanase at 70% saturation with ammonium sulphate. The results showed 1.50 fold purification after ammonium sulphate purification and 3.3 folds after gel filtration chromatography. Optimum temperature and pH of endoglucanase were 40 °C and 3 individually. Metal ion effect on endoglucanase activity was observed by using different metals. The endoglucanase activity was repressed by Fe3+ and Hg2+ and increased by Co2+ and Mn2+. The activity of endoglucanase was also found to be enhanced by organic solvents i.e. methanol, glycerol and acetone, while lessened by ethanol and isopropanol. Similarly, SDS stimulated enzyme activity, while Tween-20 decreased it. Increased amount of inhibitor like (EDTA) decreased the endoglucanase activity. The values of Km and Vmax were 4.5 mM and 65 µM/mL/min respectively.